Analysing productivity and finding solutions to improve productivity at the GLS plant of a selected lamp manufacturing factory in Bangladesh. (28th July 2021) - Islam, Md Shafiqul; Samad, Muhammad Abdus; Sarkar, Pradip; Rahman, Taufiqur; Ahmed, Mohiuddin
Bangladesh is emerging in many manufacturing industries. To ensure sustainable economic growth and compete in the global market, the industries should utilise their resources properly. Higher productivity ensures higher utilisation of available resources, i.e., man power, raw materials, etc. In this paper we have studied and analysed the productivity of a lamp manufacturing factory's GLS plant. The focus of the study was labour productivity and defects in the production floor. Labour productivity was measured and analysed using Kurosawa's structural approach for productivity measurement. It was found that the labour productivity is not up to the standard level. The reasons that reduce labour productivity and the factors for improving labour productivity were identified using questionnaires and observations. Occurrence of defects was analysed using Pareto analysis which helped to identify the vital defects. Using root cause analysis, cause and effect diagram was generated and the reasons of the defects were identified. Based on that, the solutions for reducing those defects were recommended. Some of the techniques that the lamp manufacturing factory can implement are work study, lean tools, JIT, Six Sigma and nominal group technique.